THE DEPICTION OF THE ROMANIAN COMMUNITY'S UNHEARD VOICES IN I MUST BETRAY YOU: SUBALTERN ANALYSIS - Umi Trinatasya; Darmawan , Ruly Indra (English Teaching Journal and Research: Journal of English Education, Literature, And Linguistics, 2024)
This subaltern study addresses the abuse of power that oppresses the subaltern. In the novel history fiction, I Must Betray You (2022) by Ruta Sepetys. This article analysis uses Gayatri Chakravorty Spivak's subaltern approach based on her essay “Can the Subaltern Speak". Spivak defines the concept of the subaltern as a marginalized group under the control of the dominant group then they do not have access to their voice. In I Must Betray You, many oppressive acts of abuse of power occur through policies, rules, and even manipulations carried out by the Romanian communist regime under leadership Nicholas Ceausescu in 1989 which put the Romanians in a position where they could not voice what they experienced. In collecting data article, the researcher used a descriptive qualitative method by taking excerpts from the narrative. The researcher also used intrinsic elements to describe the conflict that occurred in the narrative. The findings and discussion of this research are divided into 3 main points; the depiction of characteristics, plot using Freytag's pyramid and theme. Through these 3 main points, the researcher concluded that the depiction through each of these elements becomes connected, so that the author can describe the subaltern from various perspectives.